2017
DOI: 10.1007/s10840-017-0264-4
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of the negative component of the unipolar electrogram as a local procedural endpoint during paroxysmal atrial fibrillation catheter ablation using contact-force sensing: the UNIFORCE study

Abstract: Unipolar atrial signal analysis combined with CF sensing ensures a robust 2-year SR maintenance rate in the treatment of PAF. Clinical trial registration-URL: http://www.clinicaltrials.gov . Unique identifier: NCT02520960.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Combined data analysis demonstrated that annotated distance to site 2 was significantly greater with ACCURESP™ "on" versus "off" (i.e. 6.7mm versus 5.2mm, p=0.02), while the observed difference in site 1 RF duration 12 (15.7s versus 15.1s, p=0.09) and FTI (240g.s versus 198g.s, p=0.38) was not statistically significant.…”
Section: Resultsmentioning
confidence: 81%
“…Combined data analysis demonstrated that annotated distance to site 2 was significantly greater with ACCURESP™ "on" versus "off" (i.e. 6.7mm versus 5.2mm, p=0.02), while the observed difference in site 1 RF duration 12 (15.7s versus 15.1s, p=0.09) and FTI (240g.s versus 198g.s, p=0.38) was not statistically significant.…”
Section: Resultsmentioning
confidence: 81%
“…It has been reported that the USM is a useful guide for the endpoint of each RF application while performing the PVI. [5][6][7]19 In some cases, however, the USM did not translate into damage creation. 20 To create transmural and irreversible (rather than functional and potentially reversible) lesions, extended RF applications for a few seconds after the negative component of the USM are needed.…”
Section: Discussionmentioning
confidence: 99%
“…4 R morphology achievement, the so-called the unipolar signal modification (USM), has been reported as a useful guide for the endpoint of each RF application and provides a real-time evaluation of the transmural lesion creation while performing the PVI. [5][6][7] During RF ablation, a lesion is created by resistive heating followed by conductive heating. Resistive heating immediately causes irreversible myocardial tissue injury with cellular death, whereas conductive heating passively extends to deeper tissue layers causing potential reversible tissue damage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise Bortone et al showed in a closed-dog model that elimination of the negative component of the unipolar atrial electrogram reflects, in general, irreversible transmural necrosis creation [5] . Of interest, the same research group described recently a CF-guided ablation strategy in which RF is continued 5 to 15s after elimination of the negative component which apparently was obtained in all applications [21] .…”
Section: Loss Of the Terminal S Wave In Unipolar Electrogramsmentioning
confidence: 99%